Política oficial de preservação em Vitória : análise de uma trajetória, 1900-2000 - Salvalaio, Renata Cerqueira do Nascimento (2008)
It analyzes the official politics directed toward the preservation of the built cultural patrimony of Vitória throughout century XX, searching to situate the question inside the national context of protection of this patrimony. It was possible to establis